We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
0
23
1
avatar

Let C be the circle with equation \(x^2-6y-3=-y^2-4x\). If (a,b) is the center of C$ and r is its radius, what is the value of a+b+r?

 Oct 9, 2019

Best Answer 

 #1
avatar+19324 
+2

Let's put the circle in standard form  

 

x^2 + 4x +y^2 -6y = 3    now 'complete the square'on x and y

(x+2)*2 + (y-3)^2 = 3  +4+9

(x+2)^2 + (y-3)^2 = 4^2           so the center   is  (a,b) = (-2,3)   and the radius is 4       a+b+r = 5

 
 Oct 9, 2019
 #1
avatar+19324 
+2
Best Answer

Let's put the circle in standard form  

 

x^2 + 4x +y^2 -6y = 3    now 'complete the square'on x and y

(x+2)*2 + (y-3)^2 = 3  +4+9

(x+2)^2 + (y-3)^2 = 4^2           so the center   is  (a,b) = (-2,3)   and the radius is 4       a+b+r = 5

 
ElectricPavlov Oct 9, 2019

8 Online Users

avatar